(untitled) (Pragyaratna प्रज्ञारत्न, 2024)
Agriculture plays a vital role in Nepal’s economy, with women, particularly in rural areas, comprising a significant portion of the workforce. This paper explores gender dynamics in agriculture in Changunarayan Municipality, Bhaktapur, focusing on women’s roles in food production, resource management, and decision-making. Despite their substantial involvement, women face disparities in asset ownership and access to resources. Based on field observations and surveys of 60 households, purposively selected from two agriculture dominated communities located in two different wards of selected municipality, the study reveals that women are primarily responsible for key agricultural tasks, labor managements, and financial decisions. However, their contributions are undervalued, and they often lack tools to boost productivity. The findings emphasize the need for equitable resource distribution and greater recognition of women’s roles for sustainable agricultural development. The study concludes that future strategies should prioritize equitable access to resources, ownership rights, and tools that empower women in agriculture.